KEDAYAAN NILAI INDIGENOUS BALI SEBAGAI IDE KREATIF DALAM PERSAINGAN BUDAYA GLOBAL PADA ERA REVOLUSI INDUSTRI 4.0 - Gede Rai Remawa, Anak Agung (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Global culture and the presence of the 4.0 industrial revolution, should be a new spirit in design. The design whose birth was triggered by the outbursts of the 18th century industrial revolution, actually had an in tune breath with the development of the 4.0 industrial revolution, which can change lives and work fundamentally. In this era the level of cultural equality is getting higher. Designers need extra strength and effort to diversify their designs to make them more attractive without ignoring virtuosity. Innovation breakthrough is needed to increase diversity in this equation. Without different ideas, the competition for creation will always be homogeneous, not unique and become Western domination. The indigenous Bali value, which is better known as the value of local wisdom, can be a powerful inspiration to produce new designs, because the proof of its hundreds of years of worthiness has been proven to last. Vastly different from the current design that quickly disappeared and also too quickly appeared. This phenomenon can be a huge opportunity for creativity for local designers by doing innovation leap through their traditional souls. The soul of the indigenous Bali value which was explored intensely will provide spirit and a new image in the design. The combination of mastery of digital technology and understanding of the souls of indigenous Balinese can be a choice of design concepts in the competitive world of the creative world.